2020
DOI: 10.1002/anie.201915744
|View full text |Cite
|
Sign up to set email alerts
|

A General Strategy to Enhance Donor‐Acceptor Molecules Using Solvent‐Excluding Substituents

Abstract: While organic donor‐acceptor (D‐A) molecules are widely employed in multiple areas, the application of more D‐A molecules could be limited because of an inherent polarity sensitivity that inhibits photochemical processes. Presented here is a facile chemical modification to attenuate solvent‐dependent mechanisms of excited‐state quenching through addition of a β‐carbonyl‐based polar substituent. The results reveal a mechanism wherein the β‐carbonyl substituent creates a structural buffer between the donor and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 45 publications
(23 reference statements)
1
27
0
1
Order By: Relevance
“…One of the current challenges is how to rationally control the viscosity sensitivity of molecular rotor‐based probes. In this aspect, the Zhang group [108, 109] has presented excellent work by exploring the influence of π‐rich alternating carbon–carbon linkages or substituents on molecular rotor‐based fluorophores. It has been revealed that the length of the linkage strongly affects the viscosity sensitivity, likely resulting from the varying height of the energy barriers between the fluorescent planar and the dark twisted configurations.…”
Section: Discussionmentioning
confidence: 99%
“…One of the current challenges is how to rationally control the viscosity sensitivity of molecular rotor‐based probes. In this aspect, the Zhang group [108, 109] has presented excellent work by exploring the influence of π‐rich alternating carbon–carbon linkages or substituents on molecular rotor‐based fluorophores. It has been revealed that the length of the linkage strongly affects the viscosity sensitivity, likely resulting from the varying height of the energy barriers between the fluorescent planar and the dark twisted configurations.…”
Section: Discussionmentioning
confidence: 99%
“…Many existing TICT‐based fluorescent probes are push‐pull dyes employing dialkylated amino groups as the electron‐donating group (EDG). [ 15 , 16 , 17 , 18 , 19 , 20 ] Upon photoexcitation, the amino group could experience an intramolecular rotation of ≈90° with respect to the fluorophore scaffold, resulting in a perpendicular alignment in the excited state. [ 7 , 8 ] This rotation is accompanied by a complete charge separation between the EDG and the fluorophore scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the important applications of D-p-A type of molecules, most attention has been given to emissive conjugated systems other than thiophene-based systems mainly because of their lower emission quantum yields, short excitedstate lifetimes, and an inherent polarity sensitivity that leads to rapid nonradiative decay. 47 Studied compounds showed relatively high quantum yields even in strong polar solvents.…”
mentioning
confidence: 99%